Relatives' negotiations with healthcare professionals during older people's admission in an emergency department: An ethnographic study - Eva Hoffmann; Pernille Tanggaard Andersen; Christian Backer Mogensen; Christina Prinds; Jette Primdahl (Wiley, 2023)
Abstract Background Relatives are recognised as important for older patients' care and treatment. Variations in relatives' opportunities to negotiate the quality and continuity of older people's care and treatment can potentially lead to inequality in older people's access to care and treatment. Aim This study aimed to examine relatives' opportunities and strategies for negotiation with health care professionals (HCPs) during the admission of older people to emergency departments in Denmark. Materials and Methods We planned a qualitative ethnographical study employing a hermeneutic approach. Observations focused on social situations and interactions between relatives and HCPs. The analysis was guided by qualitative content analysis. Results The analysis derived one main theme, attitude to action, containing three subthemes: frustration obtaining access, presenting the case and a powerful relationship. Being active appeared to be essential to achieving possibilities for negotiation with HCPs. Discussion Inspired by Bourdieu, habitus, doxical values and institutional logics of relatives seem to affect their opportunities to negotiate with HCPs during older people's admission to an emergency department. Conclusion Active and proactive relatives seem to have better opportunities to negotiate with HCPs during older people's acute hospital admission than reactive, passive and hesitant relatives. The logic of public management and the medical profession seem to dominate and influence doxa in the EDs and put special demands on the relatives. This imbalance constitutes a risk of inequality in older people's access to health.